Sports medicine practice during COVID-19 pandemic - A "new normal" - Singh Kalra, S.; Mallick, A.; Dande, J. (International Journal of Sports and Exercise Medicine, 2020)
The COVID-19 pandemic has affected all areas of life, including sports and athletes which caused disruption to physical and psychological wellbeing leading to health impairment and loss of performance. The global sports calendar has been impacted, athletes are almost stuck indoors facing an unprecedented effect in their life. The sports medicine practitioners all over the world need to adapt to these new challenges. Resumption of training and competition while maintaining social distancing, pre participation evaluation and return to play advice for COVID positive athletes will be new task in hand. Risk assessment and mitigation measures should be in place before organizing sporting events. Because of the novel character of the virus we need to rely on recommendations based on expert opinions rather robust evidence. The aim of this paper is to highlight medical implication due to this novel disease on sports and athlete's health with emphasis on different schools of thought to guide practicing sports physicians in decision making.